Implementation Of Augmented Reality-Based Learning Media To Improve The Reading Skills Of Indonesian Migrant Workers' Children In Sb Kubu Gajah Selangor, Malaysia - Lawuna, Akra Maratsya Eka; Laksana, Sigit Dwi; Wulansari, Ayu (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The purpose of this study is to examine in more depth how the implementation of augmented reality (AR)-based learning media improves the reading skills of Indonesian migrant worker children in Kubu Gajah, Selangor, Malaysia. Migrant worker children often face challenges in accessing quality education and learning. This study uses a quantitative method with a survey. The population in this study were all students registered at the school with a total of 20 students, which can be called a saturated sample. It is done by testing prerequisites and hypotheses. Linearity Test Results: Sig = 0.000 0.05, indicating linear data. Normality Test Results: Sig (2-tailed) = 0.200 0.05, indicating normally distributed data. R-Square Test Results: R = 0.725, indicating 72.5% of reading skill variables are influenced by the use of AR media. Regression Test Results: Sig = 0.000 0.05, indicating a significant effect of AR media on reading skills.